Synthesis of 2-Substituted Benzothiazoles from 1-Iodo-2-nitrobenzenes by a Copper-Catalyzed One-Pot Three-Component Reaction - Liu, Jidan; Gui, Qingwen; Yang, Zhiyong; Tan, Ze; Guo, Ruqing; Shi, Ji-Cheng (Synthesis, 2013)
A novel method was developed for synthesizing 2-substituted 1,3-benzothiazoles through a copper-catalyzed, one-pot, three-component reaction of a 1-iodo-2-nitrobenzene with sodium sulfide and an aldehyde.
Keywords: catalysis; copper; multicomponent reactions; heterocycles; cyclizations; sulfur